Styrene Moiety-Carrying Diorganozinc Compound Preparation for Polystyrene-Poly(ethylene- co-1-hexene)-Polystyrene Triblock Copolymer Production - Lee, Jong Chul; Park, Kyung Lee; Bae, Sung Moon; Lee, Hyun Ju; Baek, Jun Won; Lee, Junseong; Sa, Seokpil; Shin, Eun Ji; Lee, Ki Soo; Lee, Bun Yeoul (Macromolecules, 2020)
Polystyrene (PS)-block-poly(ethylene-co-1-butene)-block-PS (SEBS), produced by PS-block-polybutadiene-block-PS hydrogenation, is a high-performance thermoplastic elastomer. Hydrogenation is costly and tedious, making SEBS market expansion difficult. Thus, we envisioned a new one-pot SEBS-like triblock copolymer synthetic scheme to grow PO chains from styrene moiety-carrying diorganozinc compounds by coordinative chain transfer polymerization (CCTP), followed by anionic styrene polymerization using a specially designed initiator, allowing PS chain growth from not only the styrene moieties but also the Zn-C sites. Large-scale preparation of highly pure styrene moiety-carrying diorganozinc compounds was one of the main challenges we faced, but we overcame it by synthesizing (CH2═CHC6H4CH2CH2CH2)2Zn (4), a stable and crystalline solid that worked well as a CCTP agent. This enabled the preparation of PS-block-poly(ethylene-co-1-hexene)-block-PS (SEHS), which exhibited a stress-strain curve similar to that of the commercial-grade SEBS. The SEHS dispersed better in a polypropylene (PP) matrix, allowing it to act as a better toughening agent for PP blending than the commercial-grade SEBS. Moreover, SEHS was less viscous, exhibiting better workability.
Keywords: Chain transfer polymerization; Commercial grade; Crystalline solids; Large scale preparation; Market expansions; Poly(ethylene-co-1-butene); Styrene polymerization; Toughening agents